Analisis Evolusi Terhadap Hak Pada Manusia Dari Perspektif Sejarah dan Budaya - Faturohman Faturohman; Deri Ardiari Kusumah; Suwahono wahono (Demokrasi: Jurnal Riset Ilmu Hukum, Sosial dan Politik, 2024)
Exploring the evolution of the rights possessed by humans, perspectives on history and culture, which can highlight a conceptual transformation carried out on human rights from ancient times, to the present. This evolution can be analyzed through the lens of civilization and culture, it can show how values ​​and norms can influence the understanding and implementation of human rights. The existence of human rights is based on ancient times such as Greco-Roman philosophical law, and also a further development is the influence of non-Western cultures, including traditions of human rights in Asia and other countries which can often be ignored. in the dominant narrative of history. This comparative approach can highlight the diversity of interpretations and practices of human rights in various cultures. There are challenges and opportunities to implement human rights in the modern era, including issues related to digital rights, and it can be concluded that understanding cultural and historical diversity is very important.